The Effect of Electronic Word of Mouth and Product Quality on The Purchase Decision of Somethinc Skincare Products on Tiktokshop with Brand Image as an Intervening Variable - Felia Mutiara Ardana; Edy Purwo Saputro (Jurnal Economic Resource, 2026)
This study examines how Product Quality and Electronic Word of Mouth (eWOM) influence the decision to purchase certain skincare products on TikTokShop, with Brand Image serving as a mediating factor. A quantitative survey method was used, with questionnaires distributed to 104 members of Generations Y and Z who were familiar with and had shopped at TikTokShop. SmartPLS version 4 is used for partial least squares (PLS) data analysis. The findings show that eWOM and product quality have a positive and significant impact on brand image. Although eWOM does not have a significant impact on purchasing decisions, product quality does have a positive, significant impact. In addition, brand image has a positive and significant effect on purchasing decisions. The overall R2 values of the research model for Brand Image and Purchasing Decision were 0.597 and 0.787, respectively, suggesting that independent variables adequately explained the dependent variables. These findings show how important product quality and brand perception are in fostering consumer loyalty and influencing purchasing decisions on social media-based e-commerce platforms like TikTokShop.